FLORA OF NAM KADING NATIONAL PROTECTED AREA II: 30 NEW RECORDS OF ANGIOSPERMS FOR LAOS - Tagane, S.; Souladeth, P.; Rueangruea, S.; Okabe, N.; Zhang, M.; Chayer, S.; Yang, C.-J.; Yahara, T. (Edinburgh Journal of Botany, 2017)
Thirty angiosperm species in 20 families, collected in Nam Kading National Protected Area, are recorded in Laos for the first time. Because the flora of Nam Kading is rich in endemic species, the area represents one of the core sites of plant biodiversity in Laos. To elucidate the plant diversity accurately, further intensive floristic surveys are required.
Keywords: Angiosperms; flora; Laos; new records